Legal Protection of Electronic Data and Documents in the Government Goods/Services Procurement System - Ahmad Feri Tanjung (CV. RADJA PUBLIKA, 2025)
Digital transformation in government procurement of goods/services through the Electronic Procurement System (SPSE) brings efficiency and transparency, but also creates new vulnerabilities to the security of electronic data and documents. This study aims to analyze the legal protection of electronic data and documents in SPSE, identify protection gaps, and formulate recommendations for improvement. The research method used is normative juridical with a legislative, conceptual, and comparative approach, supported by case studies and limited interviews with procurement officials and SPSE administrators. The results of the study show three main findings. First, cybersecurity vulnerabilities are still high, as evidenced by the leakage of 11,507 LPSE credential data in 2022 and 593 national cyber incidents in 2024. Second, while technical standards such as RSA encryption and two-factor authentication have been implemented, interagency compliance is uneven, and about 30% of procurement is not fully digital, creating security gaps. Third, human resource capacity is the weakest point, with a password management awareness level of only 79.81% and phishing attacks are still rampant. This study concludes that the legal protection of electronic data in government procurement still faces gaps between regulation and implementation, weak sanction mechanisms, and lack of human resource competence. Regulatory harmonization, periodic security audits, mandatory cybersecurity certification for procurement officials, and strict law enforcement against data breaches are needed. Without a comprehensive overhaul, integrity and trust in e-procurement will continue to be threatened.